Penetrance estimates for BRCA1, BRCA2 (also applied to Lynch syndrome) based on presymptomatic testing: a new unbiased method to assess risk?. Issue 7 (26th February 2018) - Evans, D Gareth; Woodward, Emma; Harkness, Elaine F; Howell, Anthony; Plaskocinska, Inga; Maher, Eamonn R; Tischkowitz, Marc D; Lalloo, Fiona
Abstract : Purpose: The identification of BRCA1, BRCA2 or mismatch repair (MMR) pathogenic gene variants in familial breast/ovarian/colorectal cancer families facilitates predictive genetic testing of at-risk relatives. However, controversy still exists regarding overall lifetime risks of cancer in individuals testing positive. Methods: We assessed the penetrance of BRCA1, BRCA2, MLH1 and MSH2 mutations in men and women using Bayesian calculations based on ratios of positive to negative presymptomatic testing by 10-year age cohorts. Mutation position was also assessed for BRCA1 / BRCA2. Results: Using results from 2264 presymptomatic tests in first-degree relatives (FDRs) of mutation carriers in BRCA1 and BRCA2 and 646 FDRs of patients with MMR mutations, we assessed overall associated cancer penetrance to age of 68 years as 73% (95% CI 61% to 82%) for BRCA1, 60% (95% CI 49% to 71%) for BRCA2, 95% (95% CI 76% to 99%) for MLH1% and 61% (95% CI 49% to 76%) for MSH2 . There was no evidence for significant penetrance for males in BRCA1 or BRCA2 families and males had equivalent penetrance to females with Lynch syndrome. Mutation position and degree of family history influenced penetrance in BRCA2 but not BRCA1. Conclusion: We describe a new method for assessing penetrance in cancer-prone syndromes. Results are in keeping with published prospective series and present modern-day estimates for overall disease penetrance that bypasses retrospective series biases.